Law and Politics in FCPA Prosecutions of Foreign Corporations - Elizabeth Acorn (Revista Direito GV)
Abstract The expansive reach of US prosecutions addressing corporate and economic crimes has piqued the interest of many commentators and scholars. This is perhaps nowhere more evident than in the enforcement of the US Foreign Corrupt Practices Act (“FCPA”) against non-American corporations. The US adopted the FCPA in 1977 to ban the payment of bribes to foreign public officials to obtain a business advantage—decades before most other countries did so and with jurisdiction over American and many foreign corporations. More than 40 years after the creation of the FCPA, this article reviews and outlines a growing interdisciplinary research agenda that considers historical, legal, and political influences on the application of the FCPA to foreign corporations. In addition to mapping the contours of this growing research agenda, the article identifies several challenges for such research and proposes potential avenues for future research that promise to deepen our understanding of why and when the US makes use of its expansive jurisdiction to prosecute foreign corporations for bribery of foreign public officials.